Recreating the past. Reenactment, archives, and tradition in Argentine folk dances (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Historically, folk dances worked critically with their past; however, under the notion of reconstruction, they were analyzed as detached from this idea. This article sought to analyze Argentine folk dances through reenactment. Based on three case studies, it argued that the folkloric archive has always been incomplete, selective, and political. Thus, each choreography assumed a distinct expression in which each body reactivated fragmented memories, generating new temporalities. Folklore consequently appeared as a living archive contested between tradition and innovation.
Keywords: Reenactment; Argentine folk dances; archive; tradition